Social inequalities in health among the elderly Desigualdades sociais em saúde entre idosos - Marilisa Berti de Azevedo Barros; Priscila Maria Stolses Bergamo Francisco; Margareth Guimarães Lima; Chester Luiz Galvão César (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of the present study was to assess social inequalities in health status, health behavior and the use of health services based on education level. A population-based cross-sectional study was carried out involving 1,518 elderly residents of Campinas, São Paulo State, Brazil. Significant demographic and social differences were found between schooling strata. Elderly individuals with a higher degree of schooling are in greater proportion alcohol drinkers, physically active, have healthier diets and a lower prevalence of hypertension, diabetes, dizziness, headaches, back pain, visual impairment and denture use, and better self-rated health. But, there were no differences in the use of health services in the previous two weeks, in hospitalizations or surgeries in the previous year, nor in medicine intake over the previous three days. Among elderly people with hypertension and diabetes, there were no differences in the regular use of health services and medication. The results demonstrate social inequalities in different health indicators, along with equity in access to some health service components. O objetivo do estudo foi avaliar desigualdades sociais no estado de saúde, comportamentos de saúde e uso de serviços segundo o nível de escolaridade. É um estudo transversal de base populacional com 1.518 idosos residentes em Campinas, São Paulo, Brasil (ISA-Camp 2008/2009). Observaram-se significativas diferenças sociodemográficas entre os estratos estudados. Idosos de melhor nível educacional, em maior proporção, consomem bebidas alcoólicas, são mais ativos fisicamente em contexto de lazer e têm padrões de dieta mais saudáveis. Apresentam, também, menor prevalência de hipertensão, diabetes, tontura, dor de cabeça, dor nas costas, deficiência visual, uso de prótese dentária e de saúde autoavaliada como ruim. Mas, não houve diferença no uso de serviços de saúde, hospitalizações, cirurgias e uso de medicamentos. Entre os hipertensos ou diabéticos, não houve diferença quanto ao uso regular de serviços de saúde e de medicamentos. Os resultados apontam a presença de desigualdades sociais em diversos indicadores de saúde e a presença de equidade no acesso a alguns componentes dos serviços de saúde.